Dienogest, a synthetic progestin, down-regulates expression of CYP19A1 and inflammatory and neuroangiogenesis factors through progesterone receptor isoforms A and B in endometriotic cells. Issue 147 (March 2015) - Ichioka, Masayuki; Mita, Shizuka; Shimizu, Yutaka; Imada, Kazunori; Kiyono, Tohru; Bono, Yukiko; Kyo, Satoru
Highlights: Dienogest (DNG), a synthetic progestin, is used for the treatment of endometriosis. We investigate the pharmacological effects of DNG in endometriotic cells. DNG down-regulates CYP19A1, inflammatory and neuroangiogenesis factors. Pharmacological effects of DNG are mediated by progesterone receptor (PR) A and B. Therapeutic efficacy of DNG seems regardless of PR isoform expression patterns. Abstract: Dienogest (DNG) is a selective progesterone receptor (PR) agonist and oral administration of DNG is used for the treatment of endometriosis. DNG is considered to act on PR to down-regulate pathophysiological factors associated with endometriosis. PR exists as two major isoforms, PR-A and PR-B, and their physiological functions are mostly distinct. It was suggested that PR isoform expression patterns are altered in endometriosis, but it is unknown whether the pharmacological effects of DNG are exerted through PR-A, PR-B or both. In the present study, we investigated the pharmacological effects of DNG through these PR isoforms on the expression of CYP19A1 which encodes aromatase and inflammatory and neuroangiogenesis factors associated with the pain and progression of endometriosis. We used immortalized human endometriotic epithelial cell lines that specifically express PR-A or PR-B in a spheroid cell culture system, and treated them with DNG. We evaluated messenger RNA (mRNA) expression of CYP19A1, prostaglandin (PG)E2 synthase (cyclooxygenase (COX)-2 and microsomal PGE2 synthase (mPGES)-1), inflammatory cytokines (interleukin (IL)-6, IL-8, and monocyte chemoattractant protein (MCP)-1) and neuroangiogenesis factors (vascular endothelial growth factor (VEGF) and nerve growth factor (NGF)) using real-time polymerase chain reaction. In addition, PGE2 production was measured by enzyme immunoassay. We found that DNG down-regulated mRNA expression of CYP19A1, COX-2, mPGES-1, IL-6, IL-8, MCP-1, NGF and VEGF, and PGE2 production in human endometriotic epithelial cell lines that specifically express either PR-A or PR-B. These results demonstrate that DNG activates both PR-A and PR-B and down-regulates the expression of pathophysiological factors associated with pain and progression of endometriosis. Our results suggest that DNG exerts therapeutic efficacy against the pain and progression of endometriosis regardless of PR isoform expression patterns.